Development of National Roads in Indonesia During the Democratic Period: The Strategies and Reality - Kurniadewi, Aulia; Kawano, Motoko; Fefta Wijaya, Andy; Haris Wanto, Alfi (Jurnal Ilmiah Administrasi Publik, 2018)
This study aims to examine the difference between Susilo Bambang Yudhoyono’s (known as SBY) administration and Joko Widodo’s (known as Jokowi) administration in managing the national road in Indonesia. A qualitative approach has been conducted by using primary and secondary data during 2005–2017. The result of this study has found that the pace of road development under the SBY presidency was relatively slower than the Jokowi presidency. The former focused more on the improvement of the quality of roads. Meanwhile, the Jokowi presidency focused more on constructing the new road network.